2012
DOI: 10.1177/0954407012455145
|View full text |Cite
|
Sign up to set email alerts
|

Water contamination effect in wet clutch system

Abstract: Water contamination in wet clutch systems can be a problem since both torque characteristics and wear resistance can be influenced by the presence of water. The present paper reveals the effect of externally added water on the wet clutch frictional performance. Commercially available standard paper-based friction plates and steel separator plates lubricated with commercially available automatic transmission fluid were investigated in a recently developed automated test rig using a well-confined experimental ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Regarding related future work, it would be interesting to continue with monitoring the health of Automatic Transmission Fluids (ATF) on-board via additional sensors attached to the machine, since the oil has a lot of information concerning the health of the automatic transmission clutches (Fatima et al, 2012). In practical settings, to offer customers a possibility to monitor a fleet of machines with diagnostics for each machine may save both money and time, as for instance potential clutch failures may be predicted well in advance before they occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding related future work, it would be interesting to continue with monitoring the health of Automatic Transmission Fluids (ATF) on-board via additional sensors attached to the machine, since the oil has a lot of information concerning the health of the automatic transmission clutches (Fatima et al, 2012). In practical settings, to offer customers a possibility to monitor a fleet of machines with diagnostics for each machine may save both money and time, as for instance potential clutch failures may be predicted well in advance before they occur.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a clutch is considered to have failed when it can no longer transmit the desired torque. The level of torque transfer in wet clutches is controlled by the generated friction in it, and a good and stable friction coefficient which keeps output torque at a required level is important (Fatima et al, 2013;Fatima, Marklund, & Larsson, 2012). Thus, clutch slippage is a result of diminishing frictional characteristics of the clutch system (Fatima et al, 2013).…”
Section: Automatic Transmission Clutchesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other work on anomaly detection from equipment, e.g by Miura et al (1998), Mäki (2003b), Marklund (2010), Ito et al (2012), Fatima et al (2012), Okabe (2009), Berglund (2013, the anomaly detection is made in test-rigs, but not in the actual heavy duty machines. In our application clutch slippage detection and diagnoses are done on-board the equipment where streams of sensors are processed on the machine by SVALI using a CAN bus wrapper.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies by the authors 11,12 showed that the antishudder behavior and friction stability of a wet clutch system can be hindered by increasing friction and negative friction-velocity relationship, when water has been added to the ATF. As mentioned before, both these friction outcomes, increasing friction level and negative slope of the friction-velocity curve, are not favorable conditions for a proper clutch function.…”
Section: Introductionmentioning
confidence: 99%